Mapping the branching pattern of the middle cerebral artery in the camel (Camelus dromedarius): a comprehensive anatomical analysis - Al Aiyan, Ahmad; Balan, Rinsha (Frontiers in Veterinary Science, 2023)
The complex branching structure of the middle cerebral artery serves as a crucial component in the blood supply to the cerebral cortex, playing a key role in sustaining brain function and overall neurological health in mammals. A thorough understanding of the branching structure of the middle cerebral artery is required for the advancement of veterinary medicine and neuroscience research.In this study, we provide the first comprehensive anatomical analysis of the branching structure of the middle cerebral artery (MCA) in the dromedary brain. To date, no study has examined the MCA branches in dromedaries. By examining 80 cerebral hemispheres from freshly slaughtered male dromedary camels aged 2-6 years, we aimed to explain the origin, course, and branching patterns of the MCA in the dromedary camel. Advanced casting techniques using colored latex, epoxy paint, and liquid plastic have been used to create precise renderings of the MCA structure.Our findings revealed that the MCA is the principal branch of the rostral cerebral artery and serves as the primary blood supply to the telencephalon in dromedaries. The main trunk of the MCA splits into several cortical branches, each supplying blood to a specific cerebral hemisphere. These branches comprise the rostral and caudal olfactory arteries; orbital artery; superior, middle, and inferior frontal arteries; rostral, middle, and caudal parietal arteries; and dorsal, middle, and ventral temporal arteries. This groundbreaking work considerably advances our understanding of the dromedary cerebrovascular system by providing insightful information on the anatomy and topography of the MCA. Our findings open new avenues for advancements in veterinary medicine and neuroscience research, with potential applications in the diagnosis and treatment of neurological disorders in dromedary camels. Furthermore, understanding the unique branching pattern of the MCA may have implications for comparative neuroanatomy and the evolution of cerebrovascular systems across species.